APAKAH TOTAL QUALITY MANAGEMENT MENINGKATKAN MUTU SEKOLAH MENENGAH ATAS DI KOTA CIREBON? - Asep Kurniawan (JURNAL AL-TANZIM, 2020)
This paper aims to determine the implementation of total quality management in state and private senior high schools in Cirebon City and to compare the level of their implementation. This research is a descriptive exploratory study. The instrumens of collecticting data are questionnaires, observation and interviews. Data are analyzed using descriptive and statistical t-test. The analysis finds that total quality is implemented by state and private high schools. However, the level of application is significantly different (t-value = 9,208, p-value = <0,0001). State senior high schools applys it very well, and private schools applys it well. The Differences of total quality management are in all measured aspects. The observation shows that the state senior high schools implemented maximum total quality management, while the private senior high schools implement it not optimally, due to limited resources. The implication is the higher organization's resources, the more optimal implementation of total quality management.